Highly accurate mtGenome haplotypes from long-read SMRT sequencing can distinguish between monozygotic twins. (July 2020) - Chen, Lu; Wang, Jiaqian; Tan, Lu; Lu, Chaolong; Fu, Guangping; Fu, Lihong; Zhang, Xiaojing; Wang, Qian; Ma, Chunling; Cong, Bin; Li, Shujin
Highlights: We presented a long-read SMRT sequencing strategy to identify accurate mitotypes. It may be applied to identify low-level variants between MZ twins. The reliable mitotypes generated barely have NUMTs and algorithm-derived errors. SMRT technology may be an effective tool for discriminating between MZ twins. It may be applicable in forensics, once optimized for minute or degraded specimens. Abstract: Discriminating between monozygotic twins (MZ) remains a challenge in the field of forensics globally. It is very difficult to find sequence variants within MZ twins, despite using ultra-deep next generation sequencing (NGS) for nuclear DNA. However, mitochondrial DNA might be a potential marker owing to its higher mutation rate and easier sequencing via NGS. Here, we aimed to introduce a long-read single molecule real-time sequencing (SMRT) strategy, with better continuity and fewer alignment errors, to obtain more accurate mitochondrial genome (mtGenome) sequence on the Sequel platform. Compared to Ion Torrent Personal Genome Machine (PGM), the long-read SMRT sequencing strategy generated highly accurate and mapped circular consensus sequence (CCS) reads and exhibited robust performance in terms of reliable repeatability, consistent coverage pattern, and balanced strands in mtGenome recovery. Moreover, the long-read SMRT strategy exhibited superior ability to not only identify accurate haplotypes but also discover a total of 785 low-level variants within 16 MZ twin pairs with threshold of 2% and 20 CCS reads with Q30 quality. Taken together, our findings suggested the long-read SMRT technology as an appreciable strategy for obtaining accurate mitotypes and providing a promising solution for distinguishing between MZ twin pairs in forensic genetics.